Factors Associated with Oral Health Literacy among Patients with Type 2 Diabetes Mellitus Attending Hospital Universiti Sains Malaysia - Norkhafizah Saddki; Muhamad Izaat bin Mohd Hashim; Noraini Mohamad (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the oral health literacy (OHL) level and its associated factors among patients with type 2 diabetes mellitus attending Hospital Universiti Sains Malaysia (USM). Material and Methods: This cross-sectional study involved 135 diabetic patients with a mean age of 62.6 years old (SD=9.05) who attended the Diabetes Outpatient Clinic at Hospital USM, a teaching hospital in the north-eastern corner of Peninsular Malaysia. The Malay version of the Oral Health Literacy Instrument (OHLI-M) was used to assess the level of OHL among respondents. An additional self-administered questionnaire was used to obtain other variables of interest. Systematic random sampling was applied in this study. The data were analyzed using an independent t-test and ANOVA to determine factors associated with oral health literacy among respondents. Results: Most respondents have at least one oral health problem (62.2%). The most common problem was cavitated tooth (42.2%). Other problems include toothache (17.8%), mobile tooth (17.8%), and swollen gums (16.3%). OHL level for most respondents (40.7%) was inadequate. The mean total OHLI-M score was 67.9 (SD=17.74). The OHL score was significantly lower in respondents with the following characteristics: female, no formal education or had primary education, unemployed, lower income group, never visited a dentist, and had swollen gums. Conclusion: The OHL of most patients with type 2 diabetes mellitus attending the Diabetes Outpatient Clinic, Hospital USM still need to be improved. Oral health problems were common in patients with type 2 diabetes mellitus in this study. This study also highlighted the link between OHL and socio-demographic factors. Improving the OHL of patients may increase their capability to obtain and understand oral health messages needed to take appropriate actions that will eventually prevent oral diseases associated with diabetes mellitus.